Common Mistakes in Writing Arabic Annexation System of The Students of The Arabic Language Education Department at The Islamic State University of Antasari Banjarmasin (ar) - Arif Rahman Hakim (AL-TA'RIB : Jurnal Ilmiah Program Studi Pendidikan Bahasa Arab IAIN Palangka Raya, 2019)
This study aims to know UIN Antasari students